Hot Pres Particle Board Characteristics Using Tanin Adhesive Result Rawwood Extraction - Siswanto; Nurul Widji Triana (Nusantara Science and Technology Proceedings, 2020)
Wood powder waste is very abundant if it is allowed to rot, which can pollute the environment, therefore wood powder can be made as a material for making particleboard. As an adhesive for the manufacture of particleboard, tannins from the extraction of mangrove bark are needed. According to Paridah and Musgrave 2006, the tannins content in mangrove bark reaches 26%. According to Hamidah 2006 mangrove bark that is dried or crushed contains an average of 20 – 30 % tannins and the content of these tannins is quite high and is very good for use in various kinds of industries. The purpose of this research is to find the optimum temperature of pressing and the amount of added tannins to obtain strong particleboard following SNI. The use of tannins is expected to be an environmentally adhesive alternative. The preparation of this particleboard is done by preparing the raw materials, extracting tannin from mangrove bark using a solvent of 96 % ethanol at a temperature of 70 0C for 3 hours, after that it is continued with the process of making particleboard by mixing between wood powder and tannins with variations of 20%, 25%, 30% and 35% with previously had been mixed with formaldehyde 2% of the weight of wood powder before pressing. Mold is made with a size of 20 x 20 cm were then pressed using a hot press with a temperature of 1100C, 1200C, 1300C, and 1400C. The result obtained was tested for the expected tensile compressive strength values according to SNI where the resulting particleboard can be used for household and industrial purposes. Tannins added as much as 30 % produce the best MOR value of 7,76 kg f/cm2 while the pressing temperature of 120 0C result in the best MOR value of 7,66 kg f/cm2